2021
DOI: 10.3389/fcell.2021.743421
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Zebrafish Cell Landscape at Single-Cell Resolution

Abstract: Zebrafish have been found to be a premier model organism in biological and regeneration research. However, the comprehensive cell compositions and molecular dynamics during tissue regeneration in zebrafish remain poorly understood. Here, we utilized Microwell-seq to analyze more than 250,000 single cells covering major zebrafish cell types and constructed a systematic zebrafish cell landscape. We revealed single-cell compositions for 18 zebrafish tissue types covering both embryo and adult stages. Single-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 63 publications
3
60
0
Order By: Relevance
“…Our input of 5,000 cells per sample was well within the 10x Genomics guidelines of 500 to 10,000. Given the previously published proportion of overall somatic cells in zebrafish testes of ∼1.4% ( 39 ), there would likely be less than 30 somatic cells in our sample, which borders the cluster threshold of 30 cells; this number diminishes for specific somatic cell types such as immune cells. Additionally, we have shown scRNA-seq underdetects immune cell gene expression as compared to bulk RNA-seq, all other factors held constant ( 60 ).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Our input of 5,000 cells per sample was well within the 10x Genomics guidelines of 500 to 10,000. Given the previously published proportion of overall somatic cells in zebrafish testes of ∼1.4% ( 39 ), there would likely be less than 30 somatic cells in our sample, which borders the cluster threshold of 30 cells; this number diminishes for specific somatic cell types such as immune cells. Additionally, we have shown scRNA-seq underdetects immune cell gene expression as compared to bulk RNA-seq, all other factors held constant ( 60 ).…”
Section: Resultsmentioning
confidence: 92%
“…The 13 datasets span five species (five human datasets ( 29–33 ); five mouse ( 32 , 34–37 ); one sheep ( 38 ); one macaque ( 33 ); one zebrafish ( 39 )), and vary widely among and between species. The relative contribution of each cell type population to the total dataset is seldom explicitly reported in the main text (of the identified studies, 23%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the teleost SCTs published to date were derived from zebrafish and are of high value for comparative immunology. Some studies are of remarkable complexity and cover the spectrum of hematopoietic cells (including various populations of innate and adaptive immune cells) in diverse tissue types of both embryonic and adult zebrafish ( 126 , 127 ). More specific scRNA-seq approaches focused on zebrafish B cells that express the macrophage-characteristic marker gene MPEG1.1 ( 117 ) or zebrafish macrophages associated with the central nervous system (CNS) that promote neurogenesis ( 128 ) and share conserved expression profiles with their counterparts in mammals ( 129 ).…”
Section: Technological Advances and Its Translation To Fish Immunologymentioning
confidence: 99%
“…Numerous studies involving single-cell studies in health and disease have identified new endothelial cell subtypes and functions 5 10 . Several scRNA-Seq studies using zebrafish embryos have revealed cellular heterogeneity and developmental trajectory during tissue and organ development in zebrafish 11 . In addition, a single cell transcriptomic atlas of day one to five zebrafish embryos has been generated recently 12 .…”
Section: Introductionmentioning
confidence: 99%